2014
DOI: 10.1182/blood-2013-11-539098
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 or CALR mutation status defines subtypes of essential thrombocythemia with substantially different clinical course and outcomes

Abstract: Key Points JAK2 (V617F)-mutated essential thrombocythemia and polycythemia vera are different phenotypes in the evolution of a single neoplasm. CALR-mutated essential thrombocythemia is a distinct disease entity not only at the molecular level, but also with respect to clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

68
514
10
28

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 525 publications
(620 citation statements)
references
References 37 publications
68
514
10
28
Order By: Relevance
“…Nangalia et al reported that CALR mutated ET patients presented with significantly higher platelet counts and lower hemoglobin than JAK2 mutated counterparts [2]. Findings in ET patients have subsequently been validated in two independent series [9,10]. In one study that included 576 patients with 2008 WHO-defined ET, 64.1% of whom were JAK2V617F mutated, 4.3% MPLW515 mutated, 15.5% CALR mutated (corresponding to 48.9% of JAK2 and MPL unmutated) and 16.1% triple negative (JAK2, MPL and CALR unmutated) patients [10], CALR mutated patients were predominantly male with lower leukocyte and hemoglobin levels and higher platelet counts than JAK2V617F mutated counterparts.…”
Section: Calreticulin Mutations In Mpn: Relevance For Diagnosis and Pmentioning
confidence: 92%
See 2 more Smart Citations
“…Nangalia et al reported that CALR mutated ET patients presented with significantly higher platelet counts and lower hemoglobin than JAK2 mutated counterparts [2]. Findings in ET patients have subsequently been validated in two independent series [9,10]. In one study that included 576 patients with 2008 WHO-defined ET, 64.1% of whom were JAK2V617F mutated, 4.3% MPLW515 mutated, 15.5% CALR mutated (corresponding to 48.9% of JAK2 and MPL unmutated) and 16.1% triple negative (JAK2, MPL and CALR unmutated) patients [10], CALR mutated patients were predominantly male with lower leukocyte and hemoglobin levels and higher platelet counts than JAK2V617F mutated counterparts.…”
Section: Calreticulin Mutations In Mpn: Relevance For Diagnosis and Pmentioning
confidence: 92%
“…Of importance, these subjects had longer thrombosis-free survival, and a thrombotic rate that was about onethird lower than JAK2V617F and MPLW515 mutated and similar to triple negative patients. Preliminary evidence, although not in a multivariate analysis, also indicated that CALR mutated ET patients had a lower incidence of transformation to either PV or acute leukemia compared with JAK2V617F mutated [9], whereas the incidence of PET-MF was similar to JAK2 and MPL mutated patients [9,10]. In summary, current evidence suggests that ET patients with CALR mutations are at lower risk of thrombosis and hematologic progression than those harboring the JAK2V617F mutations and this may have implications for risk stratification and management.…”
Section: Calreticulin Mutations In Mpn: Relevance For Diagnosis and Pmentioning
confidence: 94%
See 1 more Smart Citation
“…7,8 In ET, CALR mutations correlated with male sex, younger age, lower leukocyte count, lower hemoglobin level and higher platelet count 8 and in PMF with younger age, higher platelet count and lower incidences of anemia, leukocytosis and spliceosome mutations. 7 Furthermore, CALR mutations in ET were associated with longer thrombosis-free survival 8,9 and in PMF with longer overall survival. 7 Before the discovery of CALR mutations in ET and PMF, we had identified mutant ASXL1 as dynamic international prognostic scoring system (DIPSS)-plus 10 and IPSS 11 independent risk factor for survival in PMF.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests showed a WBC of 30 600/µL and a platelet count of 1 031 000/µL, in association with high serum soluble IL2‐receptor (1001 U/mL), low serum IgG (712 mg/dL), and low complement CH50 levels (5 U/mL). Essential thrombocythemia (ET)1 was suspected, but JAK2 V617F gene mutation was negative. An abdominal CT revealed a huge mass within the spleen (Figure 1A).…”
mentioning
confidence: 99%